PEMETAAN KEMIRIPAN BERDASARKAN KUALITAS APLIKASI MARKETPLACE MENURUT PELANGGAN - Niko Dwi Haryanto; Anas Alrasyid Putrawidya Buana (LPPM Universitas Terbuka, 2022)
This study aims to prove the superiority of Tokopedia, Shopee, Bukalapak, JD.ID, Lazada and Zalora based on the quality of applications made by users of these applications. The sample in this study amounted to 30 people using accidental sampling technique. Operationalization of variables in this study consists of performance, reliability, features, conformance, durability, serviceability. aesthetic and perceived quality. The data analysis technique in this study used multidimensional scaling analysis. This study maps 6 marketplaces into 4 different quadrants, quadrant 1 consists of Lazada, quadrant 2 consists of Shopee and JD.ID, quadrant 3 consists of Bukalapak and quadrant 4 consists of Tokopedia and Zalora. The conclusion of this study with overall view indicate that there are 3 marketplace groups that have similarities, group 1 consists of Bukalapak and Lazada, group 2 consists of Shopee and finally group 3 consists of Tokopedia, JD.ID and Zalora. Through the division of these groups, it is assessed that group 1 (Bukalapak and Lazada) has a poor application quality, while group 2 (Shopee) has a good application quality and finally group 3 (Tokopedia, JD.ID and Zalora) has a best application quality.